Utilization of earthworm meal (Lumbricus sp) as fish meal subtitution in diets for freswater catfish (Mystus nemurus C.V) juveniles - Siska Wulan Sari; Indra Suharman; Adelina ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The purpose of this research was to know the amount of earthworm meals in the diets on growth, feed efficiency and protein retention of freswater catfish (Mystus nemurus C.V). Five isonitrogenous (30% crude protein) experimental diets was formulated to contain 0, 10, 20, 30, and 40% earthworm meal and 100, 90, 80,70,and 60% fish meal (P0, P1, P2, P3, and P4, respectively). Completely randomized design (CRD) was used in this experiment.The result showed that a diet containing 40% earthworm meal and 60% fish meal (P4) support a good specific growth rate (2.26%/day), feed efficiency (63.36%) and protein retention (30.80%). Survival rate of fish was high (95 – 100%). It this concluded that up to 60% fish meal can be substituted with earthworm meal in the diets for freshwater catfish.Key word : diet, earthworm meal, growth, Mystus nemurus, substitution